STUDY OF THE MILKFISH (Chanos chanos) CULTIVATION ON POND REARING CONTAMINATED Cd AND Pb AT KALANGANYAR, SIDOARJO REGENCY EAST JAVA TOWARDS THE HISTOPATHOLOGY OF HEPAR, KIDNEY AND GILLS - Maftuch Maftuch; Marsoedi Marsoedi; Vendrita Damayanti Putri; Mohammad Holil Lulloh; Febi Kesid Haryo Wibisono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2015)
The objective of this research was conducted to study heavy metals content of Cadmium (Cd) and Plumbo (Pb) in cultivation rearing of milkfish (Chanos chanos) in fishpond at Kalanganyar Sidoarjo towards the effect of histopathological gills, heart, and kidney of milkfish. Research and sampling of water and milkfish carried out in the Kalanganyar village of Sedati District, Sidoarjo. The method used was descriptive method. Data was analyzed by ANOVA, LSD, and regression analysis based on the value of scoring. The result of the research showed that the water conten of Cd was <0,0024 mg/L and Pb was <0,0044 mg/L. And in sediment content of Cd was 1,079 mg/L and Pb was undetected. The result of histopatological investigatiaon of milkfish organs showed that: 1. Gills demage was hyperplasia, fusion and necrosis. 2. Hepar demage was hipertropy, kongesti, and cells degeneration. 3. Kidney demage was atrophy, cloudy swelling and glomerular hyalinization. The results of water quality investigation was temperature: 29,2 oC; pH: 7,5; DO: 6,2 mg/L; and salinity: 17,8 ppt. Keywords: Histopatology, Gill, Heart, Kidney, Milkfish, Heavy metals Cd and Pb.